Nuclear power plant closures and local housing values: Evidence from Fukushima and the German housing market - Thomas K. Bauer; Sebastian T. Braun; Michael Kvasnicka (Journal of Urban Economics, 2017)
The Fukushima Daiichi accident in Japan in March 2011 caused a fundamental change in Germany's energy policy which led to the immediate shut down of nearly half of its nuclear power plants. Using data from Germany's largest internet platform for real estate and employing a difference-in-differences approach, we find that Fukushima reduced housing prices near nuclear power plants that were in operation before Fukushima by 4.9%. Housing prices near sites that were shut down right after the accident even fell by 9.8%. Our results suggest that on the German housing market, the negative economic effects of the closure of nuclear power plants dominate potential positive changes in local amenities.
Keywords: R31; Q48; Q58; 330; Fukushima; Nuclear power plants; Housing prices; Germany